Ahj
contestada

So, I really need help with functional notation...If anyone could help me solve these problems, I'd be extremely grateful!!

Given the function G ( x ) =sqrt 2x-1 , find the value G (1), G(0), G(5), G(-4).
Given the function F ( x ) = x^2 - 3 x + 1, find the value F (-3), F(0), F(1).
Given the function H ( x ) = 3 x - 1, find the value H (2).

Respuesta :

[tex]g(x)=\sqrt{2x-1}[/tex]
[tex]g(1)=\sqrt{2(1)-1}=\sqrt{2-1}=\sqrt{1}=1[/tex]
[tex]g(0)=\sqrt{2(0)-1}=\sqrt{0-1}=\sqrt{-1}=i[/tex]
[tex]g(5)=\sqrt{2(5)-1}=\sqrt{10-1}=\sqrt{9}=3[/tex]
[tex]g(-4)=\sqrt{2(-4)-1}=\sqrt{-8-1}=\sqrt{-7}=i\sqrt{7}[/tex]

[tex]f(x)=x^{2}-3x+1[/tex]
[tex]f(-3)=-3^{2}-3(-3)+1=9-(-9)+1=19[/tex]
[tex]f(0)=0^{2}-3(0)+1=1[/tex]
[tex]f(1)=1^{2}-3(1)+1=-1[/tex]

[tex]h(x)=3x-1[/tex]
[tex]h(2)=3(2)-1=5[/tex]
ACCESS MORE